Marketing with colours and its effect on customer purchasing behaviour Survey research for opinions of customers for certain sales in Misan - Hind Naeem Hoshi ((Humanities, social and applied sciences) Misan Journal of Academic Studies, 2021)
The current research problem focuses on marketing with colours, which representing a modern marketing concept followed to influence the customer's buying behaviour. This conception is considered one of the main features for the product, that has an essential role in influencing the customer and evaluation the product that is strongly related to the preparation and willingness to buy it. This research is based on two hypotheses: correlation and influence. The study was applied to some sales centres in Misan governorate within a sample consisting of (350) customers., A questionnaire was  employed  as a tool to collect information. Statistical tools and methods were employed to analyze and interpret the data using the statistical program (SPSS V.21). This research found a set of conclusions, including sales centres' interest with colours to market their products and influence the customer’s purchasing behaviour according to society’s common cultural and social environment.  Based on these conclusions, some recommendations were made, such as the sales centres should focus more on the issue of colours in marketing by relying on marketing specialists. In addition sales centres should  choose  suitable colours for the community’s taste and age , to achieve the marketing goal